Schwarzschild-de Sitter and Anti-de Sitter Thin-Shell Wormholes and Their Stability - M. Sharif; Saadia Mumtaz (Advances in High Energy Physics)
This paper is devoted to construct Schwarzschild-de Sitter and anti-de Sitter thin-shell wormholes by employing Visser’s cut and paste technique. The Darmois-Israel formalism is adopted to formulate the surface stresses of the shell. We analyze null and weak energy conditions as well as attractive and repulsive characteristics of thin-shell wormholes. We also explore stable and unstable solutions against linear perturbations by taking two different Chaplygin gas models for exotic matter. It is concluded that the stress-energy tensor components violate the null and weak energy conditions indicating the existence of exotic matter at the wormhole throat. Finally, we find unstable and stable configurations for the constructed thin-shell wormholes.